Pelaksanaan Evaluasi Pembelajaran PAI Kurikulum Merdeka di SMK 3 Klaten - Nurul Latifatul Inayati; Silmi Syahidatun Nisa Abdillah; Fatimah Khoirunnisa; Maliyya Rahma Nur Fatikha; Zulfa Fathimatuz Zahra (STIKes Ibnu Sina Ajibarang, 2025)
Education is the most important factor in improving the quality of human resources, to achieve good quality education, the system in education must be improved starting from the student component, technology, curriculum to evaluation. Currently, based on the policy set by the minister of education Nadiem Makarim, the independent curriculum is implemented to give students the freedom to explore their abilities, but the facts in the field are that there are still many teachers who have not carried out evaluation activities ideally and continuously from time to time, therefore this research was conducted to find out the implementation of special evaluations in independent curriculum PAI learning at SMK 3 Klaten. This research activity was carried out with a qualitative research type with a case study at SMK 3 Klaten. The results of the study explain that the implementation of the evaluation of independent curriculum PAI learning at SMK 3 Klaten through assessment, namely attitude assessment, knowledge assessment and skills assessment. Attitude assessment sees how spiritual values are embedded in the character of students. Knowledge assessment looks at how the competence of spiritual knowledge possessed by participants and the last is skills assessment through project, practice and portfolio activities.